Doświadczenie kryzysu związanego z odejściem kobiet z życia zakonnego - Pieczyńska , Ewa (Kultura-Społeczeństwo-Edukacja, 2022)
The aim of the article is to describe the situation of sisters leaving the religious order and the crises they experience as a result. The first part presents the theoretical background of the research subject: information about the scale of the phenomenon, the issue of discernment a vocation and the main causes of withdrawals, and also the concept of the crisis and its types. The empirical part presents the results of research conducted among former nuns. It lists various difficulties they face and describes the various dimensions of the crises experienced by them: economical, housing, existential and emotional, as well as interpersonal and religious.